Basic researchImmunohistochemical analysis of biomarkers in patients with adenocarcinoma of the breast: correlation with menopausal status and histological grade - Vinothini, Govindarajah; Letchoumy, Paramasivame V.; Prathiba, Duvuru; Nagini, Siddavaram (Archives of Medical Science, 2008)
Introduction: Adenocarcinoma of the breast is the most common cancer worldwide and accounts for the highest morbidity and mortality. The increasing global incidence of breast cancer emphasizes the need to understand the various mechanisms involved in breast tumorigenesis. We investigated the expression of steroid hormone, steroid and growth factor receptors, cytochrome P450 isoforms, oxidative stress markers, and proteins involved in cell survival and proliferation, genomic instability, and apoptosis in breast cancer patients. Material and methods: Forty-eight breast cancer patients histologically categorized as grade I, II and III, and as pre-and postmenopausal, were chosen for the study. The expression of all the markers in tumour and adjacent tissues was analysed in the same set of patients by immunohistochemical localization. Results: The expression of oestradiol, oestrogen and progesterone receptor, HER-2/neu, CYP1A1 and 1B1, 4-hydroxynonenal, 8-hydroxy-2’-deoxyguanosine, glutathione S-transferase-P, NFkb, PCNA, p53, and Bcl-2 was significantly increased, whereas the expression of Bax and caspases was significantly lower in breast tumours compared to corresponding uninvolved adjacent tissues. The magnitude of the changes was however more pronounced in premenopausal patients and in grade III tumours. Conclusions: Our results suggest that analysis of multiple signalling pathways in the same set of patients would be useful in understanding the complex genetic alterations that interplay in the development of breast tumours.